2023
DOI: 10.3390/v15112156
|View full text |Cite
|
Sign up to set email alerts
|

Current Trends of HIV Infection in the Russian Federation

Daria Ogarkova,
Anastasiia Antonova,
Anna Kuznetsova
et al.

Abstract: Russia remains one of the areas most affected by HIV in Eastern Europe and Central Asia. The aim of this study was to analyze HIV infection indicators and study trends in Russia using data from the Federal Statistic Form No. 61 “Information about HIV infection”. HIV incidence, prevalence, HIV testing and mortality rates (from 2011 to 2022), and treatment success rates (from 2016 to 2022) were analyzed. These indicators were compared across different federal districts (FDs) of Russia. The findings revealed a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The World Health Organization reported that in 2021, HIV incidence was six times higher in Russia than in the rest of Europe [1]. HIV prevalence nationally was estimated at 0.68% in 2022 [2]. Uptake of antiretroviral therapy (ART) is reported to have increased sharply since 2018, to as high as 93% of people with HIV (PWH) who are diagnosed and recorded in the Federal HIV Register [2], though with a good deal of regional variation in coverage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The World Health Organization reported that in 2021, HIV incidence was six times higher in Russia than in the rest of Europe [1]. HIV prevalence nationally was estimated at 0.68% in 2022 [2]. Uptake of antiretroviral therapy (ART) is reported to have increased sharply since 2018, to as high as 93% of people with HIV (PWH) who are diagnosed and recorded in the Federal HIV Register [2], though with a good deal of regional variation in coverage.…”
Section: Introductionmentioning
confidence: 99%
“…HIV prevalence nationally was estimated at 0.68% in 2022 [2]. Uptake of antiretroviral therapy (ART) is reported to have increased sharply since 2018, to as high as 93% of people with HIV (PWH) who are diagnosed and recorded in the Federal HIV Register [2], though with a good deal of regional variation in coverage. Injection drug use remains a major risk factor for HIV acquisition in Russia [3,4], and the proportion of people who inject drugs who are registered in the Federal HIV Register is likely relatively low.…”
Section: Introductionmentioning
confidence: 99%